Wireless Multi-Coil Transmission With a Rotating Part of the Internal Winding - Josef Pokorny; Premysl Dohnal; Petr Marcon (IEEE Open Journal of Antennas and Propagation)
This article discusses the basic principles of concentrating the radiated near non-radiant magnetic field by changing the angle of the winding sector of the spiral coils designed on a substrate for a standard PCB (printed circuit board). The relevant principles include: 1) Changing the shape and design of the movable inner part of the coil winding; together with the static part, the moving item can form a concentrated magnetic field in space, thus creating a magnetic vector. 2) The $2× 2$ matrix of these coils comprises individual resonators changing the shape of the magnetic field according to the shape, distance, and position of the receiver. Thus, the concentrated individual vectors of the field are formed by the current amplitude, azimuth, and elevation of the individual coils. Using a spare electrical circuit, we implemented the entire concept relying on the shape of the coils. This method is materialized on a hardware prototype.